The Problems of Syrian Students in the Basic Education in Turkey - Kılıc, Volkan Alparslan; Gokce, Asiye Toker (European Journal of Social Science Education and Research, 2020)
In this study, it was aimed to examine the educational problems of basic education students migrating from Syria encountered in the schools. The research study group involved 37 Syrian students, 4 school managers and 18 teachers who were willing to participate to the research from four different secondary schools. The study group was chosen according to accessibility criterion. The data were collected through interviews. Therefore, the data was analyzed according to the qualitative methods. In the analysis of data collected by using face to face interview technique and semi-structured interview form, the content analysis method was used. According to the research results, it was determined that Syrian students have a language problem, especially during their education. They had sufficient knowledge of the Turkish language to manage their daily lives, however, academically the knowledge was concluded as insufficient. The main problems occurring among Syrian students are communication skills and adaptation. Main causes of these two problems are the differences between the ethnic origin among the Syrians students and the integration and communication with Turkish students. The Syrian students can be divided into two group as Syrian Kurdish or Syrian Arab. Both groups indicate that it is hard to communicate with each other due to the language difference. Furthermore, the Syrian girls expressed that they have more difficulties in being accepted and making friends, which causes the feeling that they are left alone. The findings of the research reveal that Syrian parents do not visit the school and that their skills of understanding and speaking Turkish are far behind their children's ability to understand and speak Turkish. According to the students 'views, the main reason for their parents' not visiting the school is the language problem. According to the data obtained from the interviews conducted by the administrators, guidance teachers and class teachers of the schools, it has been determined that some Syrian students have problems in integration during school, lack of motivation for the classes, and a more introvert student profile compared to other students. On the other hand, it was also stated that it was uncommon that Syrian students were included or had caused for any improper circumstances at school or were involved in any disciplinary case.
Keywords: Refugee, education, Syrian students, educational problems.